2017
DOI: 10.5742/mewfm.2017.93078
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Trust Perceptions : A Comparison of Nurses in Public and Private Hospitals

Abstract: Background: Hospital organizational environment influences nurses' behaviors, attitudes and work quality. Organizational justice and trust are important organizational factors which have significant effects on the organizational and individual work outcomes. Objectives: The aim of this study was to investigate perceived organizational justice and organizational trust and their relationship in nurses of public and private hospitals in north of Iran and to compare these two groups of nurses. Methods: The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Therefore, the higher the level of perceived procedural justice, the higher the level of affect-based trust towards managers. Rajabi, Abdar, and Agoush (2017) found a positive relationship between organizational justice and trust in their research in Iran. De Boer et al (2002) suggested that when employees perceive too much injustice about the procedures in the work environment, they tend to view their managers as responsible for this.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the higher the level of perceived procedural justice, the higher the level of affect-based trust towards managers. Rajabi, Abdar, and Agoush (2017) found a positive relationship between organizational justice and trust in their research in Iran. De Boer et al (2002) suggested that when employees perceive too much injustice about the procedures in the work environment, they tend to view their managers as responsible for this.…”
Section: Discussionmentioning
confidence: 89%
“…Evidence also suggests a relationship between interactional justice and affect-based trust (Arslantaş & Dursun, 2008;Colquitt et al, 2012;Cüce, 2012). Rajabi, Abdar, and Agoush (2017) found a positive relationship between organizational justice and trust in their research in Iran. There is a high correlation between trust and justice among nurses working in private hospitals compared to the public sector.…”
Section: Discussionmentioning
confidence: 89%
“…Individuals with high OJ perception make efforts and struggle to reach the goals of the institution (Pekkarinen et al ; Johnson et al ). OJ positively correlates with job satisfaction (JS), organisational commitment (Yürür ; Fardid et al ), institutional trust (Chen et al ; Terzioglu et al ; Rajabi et al ), work ability (von Bonsdorff et al ), the effort of nurses for treatment (Motlagh et al ) and organisational citizenship, (Chang & Chang ; Yaghoubi et al ; Chang ; Sulander et al ) and negatively correlates with turnover and mobbing (Terzioglu et al ; Fardid et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The perception that supervisors and deci-sion-makers are unfair in their interaction is the determinant of negative/unfavorable attitude and behavior of the employee. The increase in justice perception related to interaction not only increases well-being (Celik, et al, 2014) and positive affectivity (Polatci, & Ozcalik, 2015), but also, organizational commitment (Cagliyan, et al, 2017;Nakra, 2014), organizational citizenship behavior (Collins, & Mossholder, 2017) and organizational trust (Rajabi, et al, 2017) are strengthened whilst counterproductive work behavior (Polatci, & Ozcalik, 2015) and turnover intention (Ribeiro, & Semedo, 2014) are reduced. Another possible positive outcome of the perception of interactional justice is the increased conscientiousness for work.…”
Section: Interactional Justicementioning
confidence: 99%